Pengelompokkan Kabupaten/Kota di Provinsi Jawa Timur berdasarkan Indikator Ketenagakerjaan - Naufalia Alfi Fuadah; Zahra Afifah Nafisah; Sri Pingit Wulandari (Ebisnis Manajemen, 2024)
Labor is one of the drivers of the regional economy because it can increase productivity and community welfare. Employment indicators are often used to assess the condition and dynamics of the labor market in a region, one of which is in East Java Province. To measure the condition and dynamics of the workforce in East Java Province, a grouping of districts/cities in East Java Province was carried out using the cluster analysis method. This method is used to group objects or data into groups that have similar characteristics in the observed data. This method is used by analyzing data starting from data collection, testing cluster analysis assumptions, determining methods and conducting hierarchical and non-hierarchical cluster analysis, interpreting the results of the analysis and drawing conclusions and suggestions. So the analysis that can be obtained from this study is the best hierarchical cluster method for classifying districts/cities in East Java Province is the complete linkage method with an optimum number of clusters of 4 clusters while for the non-hierarchical cluster method with the K-Means method with the best clusters of 4 clusters while for the non-hierarchical cluster method with the K-Means method with the best clusters of 3 clusters.